2001
DOI: 10.1034/j.1600-0447.2001.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Ward atmosphere in acute psychiatric in‐patient care: patients' perceptions,ideals and satisfaction

Abstract: Patients' perception of ward atmosphere is a clinically meaningful measure appearing to be a strong predictor of satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
110
5
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 29 publications
9
110
5
7
Order By: Relevance
“…However, the highest rating of quality of care was found for the secluded-environment dimension. This is not an unexpected finding, as the secluded environment has been identified as an important aspect for quality of psychiatric care from the staff's perspective [41,42]. In a previous interview study, the staff described good quality in psychiatric care as the patient having access to a personal space where he or she can be left in peace [42].…”
Section: Discussionmentioning
confidence: 91%
“…However, the highest rating of quality of care was found for the secluded-environment dimension. This is not an unexpected finding, as the secluded environment has been identified as an important aspect for quality of psychiatric care from the staff's perspective [41,42]. In a previous interview study, the staff described good quality in psychiatric care as the patient having access to a personal space where he or she can be left in peace [42].…”
Section: Discussionmentioning
confidence: 91%
“…The aim of this current study is to provide more insight into the relationship between patient characteristics and perceived ward climate. Based on previous findings, the demographic characteristics that might be related to perception of ward climate targeted in the present study were patients' age (Campbell, Allan, & Sims, 2014;Middelboe et al, 2001;Pedersen & Karterud, 2007), length of stay within the facility (van der Helm et al, 2014), and risk of violence (Dickens et al, 2014). With respect to pathological personality features, there are reports that psychopathy may be a key determinant of climate in forensic therapeutic settings (Harkins, Beech, & Thornton, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Climate can be seen as an aspect of program responsivity that enhances treatment effects (Beech & Hamilton-Giachritsis, 2005;Howells & Day, 2003; Ward, Day, Howells, & Birgden, 2004). Ward climate has also found to be a determinant of staff wellbeing, playing a role in staff performance and morale (Moos & Schaefer, 1987), job satisfaction (Bressington et al, 2011;Middelboe et al, 2001; Rossberg & Friis, 2004), and occupational stress (Kirby & Pollock, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in conception is more important because lead to several difficulties in relationship between patients and staff (1)(2)(3)(4). Previous studies in this field have proved the importance of psychiatric hospital environment and indicated that how this environment can be manipulated to enhance therapy.…”
Section: Introductionmentioning
confidence: 99%